2016
DOI: 10.18632/oncotarget.9073
|View full text |Cite
|
Sign up to set email alerts
|

Potential options for managing LOX+ ER− breast cancer patients

Abstract: Overexpression of lysyl oxidase (LOX) is often observed in estrogen receptor negative (ER–) breast cancer patients with bone metastasis. In the present bioinformatics study, we observed that LOX is a prognostic factor for poor progression free survival in patients with ER– breast cancer. LOX overexpression was positively correlated with resistance to radiation, doxorubin and mitoxantrone, but negatively correlated with resistance to bisphosphonate, PARP1 inhibitors, cisplatin, trabectedin and gemcitabine. LOX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Future studies will evaluate the importance of ATP7A in other cancer models, including models of spontaneous cancer. Previous studies have demonstrated that elevated LOX expression is correlated with poor survival of ER-negative breast cancer patients (38). Consistent with a requirement for ATP7A in LOX activity, we found that high ATP7A expression correlates with decreased survival in patients with ER-negative breast cancer (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Future studies will evaluate the importance of ATP7A in other cancer models, including models of spontaneous cancer. Previous studies have demonstrated that elevated LOX expression is correlated with poor survival of ER-negative breast cancer patients (38). Consistent with a requirement for ATP7A in LOX activity, we found that high ATP7A expression correlates with decreased survival in patients with ER-negative breast cancer (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Cancer Patients. Previous studies have shown that high LOX expression is correlated with reduced survival in patients with estrogen receptor (ER)-negative breast cancer (38). We used publicly available databases to investigate the degree to which patient mortality is correlated with ATP7A mRNA expression in breast tumors.…”
Section: Atp7a Expression Is Correlated With Reduced Survival In Breastmentioning
confidence: 99%
“…It has been previously reported that LOX enhances the metastatic trait of breast tumors in animals by stimulating TWIST1 expression in tumor cells (8). In addition, LOX overexpression in breast cancer has been associated with EMT of tumor cells (28). Here, LOX overexpression in Hct116 cells did not modify the morphologic appearance of these cells and it did not modify the expression of transcription factors TWIST1 and SNAI1, indicating that LOX in colorectal cancer cells did not contribute to tumor cell dissemination in bone by promoting an EMT.…”
Section: Discussionmentioning
confidence: 97%
“…It has only been reported that LOX is regulated by HIF-1α under hypoxia and is induced by TGF-β in cancer cells, the mechanisms are still largely uncovered. Studies on LOX previously focused on breast cancer ( Wuest et al, 2015 ; Han et al, 2016 ). However, we found that LOX expression is more related to the poor prognosis of lung adenocarcinoma, as is shown in Figure 1 .…”
Section: Discussionmentioning
confidence: 99%